SEASONAL INFLUENCE ON THE QUALITY AND FREEZABILITY OF SEMEN OF SWAMP BUFFALO BULLS (Indian Journal of Animal Production and Management, 2015)
A study was conducted to record the basic information on seasonal influence on the quality and freezability of semen of four swamp buffalo bulls maintained at “Network Project on Swamp Buffalo,” Department of AGB, College of Veterinary Science, Khanapara, Guwahati. The year was divided into summer (June to August), autumn (September to November), winter (December to February) and spring (March- May) on the basis of meteorological data of the area. Each ejaculate was collected biweekly by AV method to record the ejaculate volume, mass activity, initial sperm motility, sperm concentration, live sperm, total HOST reacted sperm, live intact acrosome, sperm abnormality percentage. After collection the semen samples were extended with Tris-egg yolk- citrate glycerol extender before filling in 0.25 ml French straws and assessed the freezability by examining the percentage of progressively motile spermatozoa. The results revealed that the effect of seasons was found to be significant for ejaculate volume (P< 0.01), initial sperm motility (P< 0.05), sperm concentration (P< 0.01), and total head abnormalities (P< 0.05). The ejaculate volume and sperm concentration was significantly (P
Keywords: Swamp buffalo bull; seasons; semen characteristics